Shift Happens: The Recent Evolution of Canadian Library Associations - Cleyle, Susan; van den Hoogen, Suzanne (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
Expectations weigh heavily on the shoulders of Canadian library associations. Association members and library workers increasingly demand that library associations assume the role of professional development provider, policy developer, advocate and lobbyist. As a result, associations must evaluate the landscape in which they are operating, and be prepared to align their mission, vision and values to ensure they are meeting the expectations of their respective library sectors and communities. This paper introduces five articles written by leaders in Canadian library associations that recently undertook a significant shift in their structure, focus and direction following a period of evaluation and reflection. Three guiding principles emerge from these articles: listen to your community, do not go it alone, and any shift, big or small, takes time.